Analisis Perbandingan Anggaran Biaya Operasional dan Anggaran Pendapatan dalam Menilai Kinerja Keuangan pada PT. Dunia Barusa Toyota Meulaboh - Muliati Muliati; Alfian Anas (Universitas Serambi Mekkah, 2023)
The purpose of this study was to analyze the difference between the amount of the budget and its realization and the magnitude of the influence between the operating expense budget and the revenue budget on financial performance through a comparison between the two components of the budget at PT. Dunia Barusa Toyota Meulaboh in 2021-2022. The research method used is a quantitative method with a comparative approach. The research data was obtained by obtaining primary data directly from those who play a role in compiling the company's budget. In this study the data analysis method used is multiple linear regression to calculate the quantitative comparison of a change in the occurrence of variable X to other events (variable Y). In addition, hypothesis testing is also used which consists of analysis of the statistical t-test coefficients with the level of the test used is α = 0.05. The results showed that the value of the coefficient of determination, the operational cost budget and revenue budget have a strong relationship with Return on Assets (ROA). Based on statistical tests, it was concluded that partially the operational cost budget and revenue budget had a significant effect on financial performance at PT. Dunia Barusa Toyota Meulaboh.